2009
DOI: 10.2320/matertrans.m2009177
|View full text |Cite
|
Sign up to set email alerts
|

A Ferromagnetic Resonance Study of Iron Complexes as Biologically Synthesized in Magnetic Bacteria

Abstract: In order to analyze the magnetic behaviors of iron complexes biologically synthesized in magnetic bacteria MS-1, we performed FMR (Ferromagnetic Resonance) measurements for each fraction of the cell. We observed FMR spectra from the ferric iron (Fe 3þ ) compounds distributed in each fraction of the MS-1 cell. In particular, the magnetosome fraction yielded an anisotropic FMR signal, whereas other fractions were simple FMR spectra of a Gaussian type.Upon counting the numbers of spins in various cell fractions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Intense uniaxial ESR spectral peak is indicative of large number of unpaired electrons as dangling bonds . Spin density has been calculated 4.36 × 10 24 spin/g . High spin density is due to unpaired electrons providing reactive surface sites for water molecule dissociation .…”
Section: Resultsmentioning
confidence: 96%
“…Intense uniaxial ESR spectral peak is indicative of large number of unpaired electrons as dangling bonds . Spin density has been calculated 4.36 × 10 24 spin/g . High spin density is due to unpaired electrons providing reactive surface sites for water molecule dissociation .…”
Section: Resultsmentioning
confidence: 96%
“…We report ferromagnetic resonance (FMR) and coercivity distribution characterizations on collections of uncultivated MTB that produce magnetite, co-produce greigite and magnetite, and only greigite. We show that uncultivated MTB are characterized by a wider range of FMR empirical spectral parameters compared with the five cultured magnetite-producing MTB strains that have been characterized to date [20][21][22]25,26,36,37 . We also show that compared with putative Neogene greigite magnetofossil-bearing sedimentary rocks 16,38 , the coercivity distributions of uncultivated MTB that produce magnetite, magnetite and greigite, or greigite only, are fundamentally left-skewed with a lower median.…”
mentioning
confidence: 93%
“…in the X-band range [11,27,29,36]. S-band FMR spectroscopy operates with microwave frequencies in the 4 GHz range.…”
Section: Basic Principles and Simulationmentioning
confidence: 99%
“…asymmetry of the absorption spectra) permit a direct way to detect the anisotropy of magnetosome chains [11,[27][28][29][30][31][32]. Mastrogiacomo et al [33] showed that FMR experiments of MTB using microwave frequency of 4 GHz, i.e.…”
Section: Introductionmentioning
confidence: 99%